Pelatihan Pencegahan Kekerasan Pada Anak Untuk Guru PAUD - Widayanti, Melia; Reza, Muhammad; Malaikosa, Yes Matheos Lasarus; Sya'dullah, Achmad (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2024)
Maintaining children's health and safety is a shared responsibility involving families, schools and communities, as children will develop optimally in a safe and comfortable environment. Collaboration between various parties is needed to create a supportive environment, including in schools. Data from 2023 shows that cases of violence against children in Indonesia are still very high, with adverse physical, emotional and sexual impacts on children as vulnerable individuals. Teachers as educators and protectors in schools have an important role in preventing child abuse through the right knowledge and strategies. Departing from this problem, the implementation team from the Community Service Program (PKM) PG PAUD Study Program designed a mentoring program for teachers related to efforts to prevent violence in early childhood. This program is realized in the form of training involving IGTKI teachers in Banyuwangi Regency, given the high number of child abuse cases that occur in the region. The training aims to improve teachers' ability to recognize, detect, and make preventive efforts to minimize violence against children in schools. With this training, teachers are expected to have a deeper understanding of various forms of violence, risk factors, and effective interventions. In addition, this training also aims to create synergy between teachers and the school environment in building a safe learning atmosphere, thus supporting children's maximum growth and development. This program is expected to be the first step in creating a child-friendly and violence-free school environment.